Penyusunan Laporan Keuangan Berdasarkan Standar Akuntansi Keuangan Entitas Mikro, Kecil dan Menengah (SAK EMKM) pada Bank Sampah Kalibukbuk Bersih (KALIBER) di Desa Kalibukbuk Kec/Kab Buleleng - Santiani, Putu; Astawa, I Gede Putu Banu (Universitas Pendidikan Ganesha, 2021)
From research conducted at the KALIBER Waste Bankit shows that the KALIBER waste bank customers always increase every year, but it is very unfortunate if the KALIBER waste bank has not made financial reports in accordance with SAK-EMKM. So this research was conducted with the aim of compiling Financial Statements Based on Financial Accounting Standards for Micro, Small and Medium Entities (SAK EMKM) at the Clean Kalibukbuk Waste Bank (KALIBER) in Kalibukbuk Village,Â Buleleng city. The research method is carried out using qualitative methods using data collection techniques through interviews, observations, literature studies, and documentation. From the problems encountered, the solution is to prepare financial statements in accordance with SAK-EMKM by obtaining results on the income statement for July â€“ December 31, 2020 amounting to Rp 2.176.200Â and for the balance sheet/financial position report showing the total assets and liabilities of Rp 120.215.525.Keywords: Waste bank, SAK EMKM, financial reports